2019
DOI: 10.2196/13241
|View full text |Cite
|
Sign up to set email alerts
|

Social Inequity and Structural Barriers to Completion of Ecological Momentary Assessments for Young Men Who Have Sex With Men and Trans Women Living With HIV in San Francisco

Abstract: Background Ecological momentary assessments (EMAs) administered via text messaging facilitate real-time data collection. With widespread cell phone access, EMAs are becoming more available to even the most disenfranchised communities, such as those living with HIV. However, structural barriers disproportionately burden young men who have sex with men (MSM) and trans women (TW) living with HIV and threaten participation in HIV research. Objective We aim to identify struc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…(64,65). Innovative approaches will also be needed to 1) account for disparities in access to technology (both digital devices and internet access), and 2) monitor the e cacy and safety of medication use if regular testing and viral load monitoring are limited (63,(66)(67)(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%
“…(64,65). Innovative approaches will also be needed to 1) account for disparities in access to technology (both digital devices and internet access), and 2) monitor the e cacy and safety of medication use if regular testing and viral load monitoring are limited (63,(66)(67)(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous ways of providing remote interventions. Text messaging has been used frequently for motivational messages, reminders, and ecological momentary assessments [12][13][14]. Many text messaging platforms have been developed and evaluated for HIPAA-compliant communication with participants [15].…”
Section: Intervention Provisionmentioning
confidence: 99%
“…Finally, future EMA studies would benefit from a thorough consideration of institutional and individual barriers to EMA survey completion in order to reduce missing responses. A previous analysis of Health eNav EMA data confirmed that housing instability, incarceration, competing needs, and educational constraints interfered with EMA completion for young MSM and TW, even though participants had continuous access to cellular devices [ 38 ]. While one recommendation to preemptively address participant nonresponse would be to invest in procedures that sustain retention over the follow-up period, structural barriers to such an investment (eg, systemic marginalization of the populations served or lack of grant funding) highlight the unrealistic nature of such a recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have used EMAs to capture fine-grained variations in substance use [ 28 - 31 ] and, more recently, behaviors among people living with HIV [ 28 , 32 - 34 ]. A number of studies have shown that EMA is feasible and acceptable among MSM [ 34 - 37 ] and persons who use substances [ 28 , 29 ]; one study showed moderate compliance to EMA among young MSM and TW living with HIV [ 38 ].…”
Section: Introductionmentioning
confidence: 99%